Maintaining the feasibility of hard real-time systems with a reduced number of priority levels - Qureshi, Muhammad Bilal; Alrashed, Saleh; Min-Allah, Nasro; Kołodziej, Joanna; Arabas, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
When there is a mismatch between the cardinality of a periodic task set and the priority levels supported by the underlying hardware systems, multiple tasks are grouped into one class so as to maintain a specific level of confidence in their accuracy. However, such a transformation is achieved at the expense of the loss of schedulability of the original task set.
Keywords: real-time systems; feasibility analysis; fixed-priority scheduling; rate monotonic algorithm; online scheduling